Identitas Sastra Arab Kontemporer dan Perubahan Ekonomi - Teguh Luhuringbudi (Alfaz (Arabic Literatures for Academic Zealots), 2018)
AbstractThis study proves that Arabic as an identity and as a connector between the contemporary Arabic literary products and economic changes. It can be concluded that the more faded the use of Arabic, the various Arabic cultural and literary products will be degraded and even eliminated; and the magnitude of the value of economic changes that cannot be detailed will be a deficit, especially in the field of creative industry and translation. This research is aimed to explore the significance and relevance of cultural products to the East-an. This research uses library method in the perspective of data gathering and qualitative method in data reduction perspective. The perspective used is the perspective of globalization. Stages of analysis related perspectives used are the placement of the global arena, symbiotic mutualism, and technological involvement. AbstrakPenelitian ini membuktikan bahwa bahasa Arab sebagai identitas sekaligus penghubung antara geliat produk-produk sastra Arab kontemporer dan perubahan ekonomi. Hal ini dapat disimpulkan bahwa semakin pudar penggunaan bahasa Arab, maka beragam produk budaya dan sastra Arab akan terdegradasi bahkan tereliminasi; dan besarnya nilai perubahan ekonomi yang tidak dapat didetilkan akan mengalami defisit, khususnya dalam bidang industry kreatif dan penerjemahan. Penelitian ini ditujukan untuk menggali signifikansi dan relevansi produk-produk budaya ke-Timur-an. Penelitian ini menggunakan metode pustaka dalam perspektif penjaringan data dan metode kualitatif dalam perspektif reduksi data. Perspektif yang digunakan adalah perspektif globalisasi. Tahapan analisis terkait perspektif yang digunakan ini adalah penempatan arena global, simbiosis mutualisme, dan keterlibatan teknologi.